Sugar Consumption of the Adult Age Group: Phenomenological Study - Rani Nuraeni; Samuel Maju Simanjuntak (Jurnal Berita Ilmu Keperawatan, 2023)
Sugar consumption has been associated with some diseases such as diabetes mellitus in Indonesia. Qualitative informations regarding sugar consumption patterns among adult individuals is an essential approach to construct appropriate approaches to the emerging problems. The qualitative descriptive method with the phenomenological approach of this research employed a purposive sample technique with data saturation as the number determinant. The key informants who meet the requirements and are willing to participate are given an Informed Consent to be filled in before the interview. Interviews were done by semi structured guided questions. The Colaizzi 7 steps qualitative analysis technique are used to examine the data obtained 7 key informants participated voluntarily in this study. Results: There are 3 sub-themes emerged from the verbatim data: sugar sources, adjustment of the type of sugar intake, attempts to change sugar consumption patterns, and interventions related to sugar eating habits. The three sub-themes formed three major themes: the pattern of sugar intake and consumption time in daily routine, the attempt to change the habits of sugar consumption, the approach in changing the patterns of sugar consuming habits in adults through experience and knowledge, daily practice and through health education. As a health educator, it is expected to be able to modify society’s sugar consumption habits.